The Influence of Social Media Marketing Activity, Performance Expectancy, and Effort Expectancy on Repurchase Intention through the Mediator of Behavioral Intention for Cotton Mom Products on Shopee - Rachael, Esbby; Wijaya, Sienly Veronica (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
In this research we investigate the impact of Performance Expectancy and Social Media Marketing Activity (SMM) on repurchase intentions among Millennial mothers purchasing Cotton Mom products on the Shopee platform. Utilizing a quantitative study via Structural Equation Modeling (SEM) with Partial Least Squares (PLS).Through a quantitative investigation of Structural Equation Modeling (SEM) with Partial Least Squares (PLS), responses obtained from a poll of mothers in the Millennial generation a significant positive relationship between SMM activities and Behavioral Intention, which subsequently affects Repurchase Intention. Additionally, Performance Expectancy is found to positively impact Behavioral Intention, while Effort Expectancy and Social Influence show no significant effects. The findings emphasize the importance of effective SMM strategies in driving consumer loyalty and suggest that marketers should focus on enhancing product performance perceptions to foster repurchase intentions.